How the Hotel Website Management Influence Hotel Supply Chain Management and Tourism Industry? A Case of Malaysian - Roeshartono Roespinoedji; Yati Mulyati; Rozahi Istambul; Norhisham Abdul Mutalib (International Journal of Supply Chain Management, 2019)
The objective of the current study is to examine the influence of hotel website management on hotel supply chain management and tourism industry performance in Malaysia. In the present decade, there is an increasing public interest in the web correspondence and the Internet marketing on tourism. A growing number of the Internet clients demonstrate that the Internet has grown quicker than some other type of electronic innovation or correspondence. That is why it is one of the emerging element to connect hotels and tourists. In this study a survey was carried out to collect the data from hotel employees and tourists. While analysing the data, it is revealed that hotel website management has considerable contribution in tourism industry through hotel supply chain. Website elements such as accessibility, flexibility and interactivity have important role in hotel supply chain. Moreover, staff service quality cannot be neglected. It increases the website service quality by strengthening the positive effect of hotel website on hotel supply chain.